III S"ezd narodnykh deputatov SSSR . III S"ezd narodnykh deputatov SSSR . 3rd Congress of People's Deputies of the USSR . III Съезд народных депутатов СССР - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Gorbachev's presidential inauguration ceremony. Featured in the program: Gorbachev, Mikhail Sergeevich (President of the USSR); Luk'ianov, Anatolii Ivanovich (Chairman of the Supreme Soviet of the USSR) Трансляция церемонии приведения к присяги М. С. Горбачева, вступающего в должность Президента СССР. В программе участвуют: Горбачев, Михаил Сергеевич (Президент СССР); Лукьянов, Анатолий Иванович (Председатель Верховного Совета СССР)